Gender specific cut-off points of age for disability among rural elderly in Anhui Province, China - He, Xinran; Wang, Xianwen; Zhang, Min; Zhu, Weizheng; Liu, Yuyang; Sun, Qian; Chen, Guimei; Li, Min; Ding, Hong (Frontiers in Public Health, 2022)
Objective The purpose of this study was to determine the optimal cut-off values of age for disability in order to predict the risk of disability for older adults in rural areas. Methods WHO Disability Assessment Schedule 2.0 was used to assess disability. The cut-off values of age for disability were obtained by ROC curve analysis. Results The cut-off points of age for cognition restriction, mobility restriction, self-care restriction, getting along with people restriction, life activities restriction, and social participation restriction for men were 70.5, 68.5, 72.5, 70.5, 71.5, and 68.5 years old, respectively. The cut-off points of age for cognition disability, mobility restriction, self-care disability, getting along with people disability, life activities disability, and social participation disability for women were 72.5, 71.5, 70.5, 70.5, 71.5, and 71.5 years old, respectively. Over the cut-off values of age was an independent risk factor for disability (P < 0.05). Conclusion Presenting first disability symptoms were different between men and women. Preventive efforts to prevent future disability should be different for men and women.